Can People Intentionally and Selectively Forget Prose Material? - Pastötter, Bernhard; Haciahmet, Céline C. (Frontiers in Psychology, 2022)
List-method directed forgetting (LMDF) is the demonstration that people can intentionally forget previously studied information when they are asked to forget what they have previously learned and remember new information instead. In addition, recent research demonstrated that people can selectively forget when cued to forget only a subset of the previously studied information. Both forms of forgetting are typically observed in recall tests, in which the to-be-forgotten and to-be-remembered information is tested independent of original cuing. Thereby, both LMDF and selective directed forgetting (SDF) have been studied mostly with unrelated item materials (e.g., word lists). The present study examined whether LMDF and SDF generalize to prose material. Participants learned three prose passages, which they were cued to remember or forget after the study of each passage. At the time of testing, participants were asked to recall the three prose passages regardless of original cuing. The results showed no significant differences in recall of the three lists as a function of cuing condition. The findings suggest that LMDF and SDF do not occur with prose material. Future research is needed to replicate and extend these findings with (other) complex and meaningful materials before drawing firm conclusions. If the null effect proves to be robust, this would have implications regarding the ecological validity and generalizability of current LMDF and SDF findings.